Penerapan Strategi Pelaksanaan SP (1-4) Dengan Masalah Keperawatan: Defisit Perawatan Diri Di UPT Pelayanan Sosial Tuna Susila Dan Tuna Laras Dinas Sosial Provinsi Sumatera Utara - Herianto Bangun; Arianus Zebua; Fransiskus Mendrofa (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
This community service aims to enhance the quality of life and independence of residents in the Social Rehabilitation Center for the Disabled (UPT) through appropriate nursing interventions. The community service method involves a participatory approach, where collaboration between the team and relevant stakeholders is employed to design and implement the SP (1-4) strategy. The steps include problem identification, intervention planning, action implementation, and result evaluation. The evaluation results also indicate that the implementation of this strategy can be adopted and adapted to the needs of similar service units in various contexts. In conclusion, the application of the SP (1-4) implementation strategy is effective in improving self-care and the quality of life of residents at the Social Rehabilitation Center for the Disabled. The implications of this community service can serve as a reference for similar institutions and relevant stakeholders to develop intervention models that are suitable for the context and characteristics of the served community.